Graded holey Nickel Cobalt layered double hydroxide nanosheet array electrode with high mass loading for high-energy-density all-solid-state supercapacitors - Yang, Tianyi; Ye, Qinglan; Liang, Yingxue; Wu, Liuyi; Long, Xiaoli; Xu, Xuetang; Wang, Fan (Journal of power sources, 2020)
Sophisticated design and fabrication of nanostructure electrodes is a prerequisite to meet the requirements of high-performance supercapacitors. In this work, the growth behavior of NiCo layered double hydroxide (LDH) nanosheet arrays in different ethanol/water solutions is explored, and graded holey NiCo LDH nanosheet arrays (G-NiCo LDH) with interpenetrated caverns are obtained on carbon cloth substrate. Caverns of small size are formed at the bottom of the nanosheet arrays. The graded holey nanoarrays contain free open space between the nanoarchitectures for electrolyte access, are largely free of “dead volume”, and ensure strong adhesion of nanosheets. The as-obtained nanostructured electrode with high mass loading (6.02 mg cm−2) shows excellent specific capacitance of 1497 F g−1 (9.03 F cm−2) at 5 mA cm−2 and high cycling stability. A high-performance all-solid-state G-NiCo LDH//activated carbon asymmetric supercapacitor is then assembled. This device exhibits a maximum working voltage of 1.8 V, an extraordinary specific capacitance of 241 F g−1 at 1 A g−1, a prominent energy density of 108 Wh kg−1 at a power density of 900 W kg−1, and excellent cycling stability (93% capacitance retention after 8000 cycles). This work opens an innovative avenue toward the design of hierarchical electrodes for future energy storage devices. [Display omitted] •Graded holey NiCo LDH nanosheet arrays with interpenetrated caverns are obtained.•Electrode with high loading of 6.02 mg cm−2 shows the capacitance of 9.03 F cm−2.•All-solid-state asymmetric supercapacitor delivers 108 Wh kg−1 at 900 W kg−1.